The Drama of Masculinity and Medieval English Guild Culture - Fitzgerald, C. author. aut Link
XIII, 214 p.
Keywords: This study argues that late medieval English 'mystery plays' were about masculinity as much as Christian theology, modes of devotion, or civic self-consciousness. Performed repeatedly by generations of merchants and craftsmen, these Biblical plays produced fantasies and anxieties of middle class, urban masculinity, many of which are familiar today.